The Relationship between D-dimer test and COVID-19 (Journal of Academic Research, 2024)
Background: COVID-19 is common disease in the world, and it has caused many complications to humans, D-dimers have been shown to be of prognostic value in various diseases, including cardiovascular disease and cancer, and D-dimer is currently the best available marker for COVID-19 associated hemostatic abnormalities. The objective of this study was found the relationship between D-dimer and COVID-19 in the patients.  Methods: In this study 3913 samples were collected from patient with COVID-19, from January 2020 to April 2021,  A D-dimer test was conducted at the Misurata Central Laboratory, the Most of the cases that have a high D-dimer protein result have serious complications such as thrombosis and pulmonary embolisms.The normal range of D-dimer was taken as